2021
DOI: 10.1111/jsr.13276
|View full text |Cite
|
Sign up to set email alerts
|

Imagery rehearsal therapy and/or mianserin in treatment of refugees diagnosed with PTSD: Results from a randomized controlled trial

Abstract: Sleep disturbances are frequently part of the symptomatology in refugees with post‐traumatic stress disorder (PTSD). It has been suggested that targeting sleep disturbances may enhance the outcome of PTSD treatment. However, randomized studies on the effect of treatment focusing on sleep disturbances in refugees with PTSD are lacking. The aim of this study was to examine add‐on treatment with imagery rehearsal therapy (IRT) and/or mianserin against treatment as usual (TAU) alone in a sample of trauma‐affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…The bias varies from negligible (−0.04 scale points) to substantial overestimation for the group of female patients with 5–10 years since trauma (0.40 scale points). In particular, the latter is an issue for further investigation, as the effect size with regard to improvement in PTSD in Danish treatment-seeking refugees measured with the HTQ has been found to be 0.33 for a group receiving imagery reversal therapy compared to treatment as usual (Sandahl et al, 2021 ) – an effect that may be contaminated by gender and/or time since trauma bias. The degree to which the bias discovered in this study would affect the prevalence PTSD in females is also an issue for further research, as previous research has shown higher prevalence rates in, for example, UK and Israeli trauma-exposed females than in males (McGinty et al, 2021 ), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The bias varies from negligible (−0.04 scale points) to substantial overestimation for the group of female patients with 5–10 years since trauma (0.40 scale points). In particular, the latter is an issue for further investigation, as the effect size with regard to improvement in PTSD in Danish treatment-seeking refugees measured with the HTQ has been found to be 0.33 for a group receiving imagery reversal therapy compared to treatment as usual (Sandahl et al, 2021 ) – an effect that may be contaminated by gender and/or time since trauma bias. The degree to which the bias discovered in this study would affect the prevalence PTSD in females is also an issue for further research, as previous research has shown higher prevalence rates in, for example, UK and Israeli trauma-exposed females than in males (McGinty et al, 2021 ), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Data are exclusively collected at the CTP, and the municipalities are not involved in data collection and processing of the RCT. Five randomised controlled trials aiming to increase knowledge on the treatment of trauma-affected refugees been carried out at the CTP (17)(18)(19)(20)(21). The trauma-affected refugees referred to the CTP derive from various countries, the majority originating from Syria, Iraq, Afghanistan, Iran, and Lebanon.…”
Section: Participants and Study Settingmentioning
confidence: 99%
“…Both studies stress that the quality of evidence for their ndings is moderate as the studies included are small with limited methodological quality. Five randomised controlled trials (RCTs) carried out at the mental health clinic of this trial protocol have investigated the outcomes of different treatment modalities for traumaaffected refugees (psychotherapy, psychopharmacological treatment, physical activity, and sleep disturbance targeted therapy) (17)(18)(19)(20)(21). All ve studies found a limited treatment effect on PTSD symptoms, which could be explained by the often chronic state of PTSD in refugees.…”
mentioning
confidence: 99%
“…The TRIM has demonstrated a high-inclusion rate, at over 85% of the patients receiving treatment at the CTP, and has enabled an unprecedented series of randomized trials with trauma-affected refugees. [16][17][18][19][20] Anticipating the advent of the ICD-11, the CTP has integrated the first part of the ITI into the standard assessment for PTSD. This covers the ICD-11 PTSD symptoms and can typically be administered within a single session.…”
Section: Introductionmentioning
confidence: 99%